Physical and in-vitro evaluation of pure and substituted MxCe1-xO2 (M = Co, Fe or Ti and x = 0.05) magnetic nanoparticles. Issue 7 (1st April 2021) - Alla, S.K.; Gangwar, A.; Shaw, S.K.; Viswanadh, M.K.; Neogi, K.; Muthu, M.S.; Gupta, Nidhi; Meena, Sher Singh; Kollu, P.; Mandal, R.K.; Prasad, N.K.
Abstract: High resolution TEM studies revealed the spherical morphology of Mx Ce1-x O2 (M = Co, Fe or Ti, x  = 0.05) particles with their size in the range of 8–11 nm. Raman, UV and PL spectroscopy analyses evidenced that oxygen vacancy concentration modified with the type of dopants. The concentration of vacancies in the Co0.05 Ce0.95 O2 sample was relatively higher and hence it had optimum magnetization value. The in-vitro cytotoxicity study for Mx Ce1-x O2 (M = Co, Fe or Ti, x  = 0.05) nanoparticles against human lung adenocarcinoma (A549 cells) was conducted. The results suggested that at a 10 μg/mL concentration, the undoped CeO2 nanoparticles have shown cell viability up to 99%. In contrast, at the same concentration, the doped CeO2 such as Co0.05 Ce0.95 O2, Fe0.05 Ce0.95 O2 and Ti0.05 Ce0.95 O2 nanoparticles demonstrated the cell viability of ~97%. Furthermore, the samples displayed reliable biocompatibility up to 1000 μg/mL concentration. Interestingly, Co-doped CeO2 nanoparticles exhibited relatively higher biocompatibility against A549 cells at all concentrations. Further, the higher amount of vacancies might have improved the free radical scavenging effect and so the biocompatibility for the samples.